Novel HIVEP2 Variant p.Q1248* is Associated with Developmental Delay: A Case Report - Jain, Angita; Atwal, Paldeep S. (Journal of Pediatric Genetics, 2019)
In this report, we describe a 5-year-old boy with global developmental delay who presented for medical genetic evaluation. We performed whole exome sequencing that revealed the involvement of a heterogenous variant p.Gln1248Ter (CAG > TAG): c.3742 C > T inherited de novo in exon 5 of HIVEP2 (human immunodeficiency virus type I enhancer binding protein 2; NM_006734.3). The gene variant p.Q1248* is interpreted to be associated as a cause of the intellectual disability. We review pathomechanisms of HIVEP2 and discuss the reasoning behind the pathogenicity of this novel variant. To the best of our knowledge, this the first reported case that demonstrates the p.Q1248* variant as pathogenic.
Keywords: HIVEP2 variant; developmental delay; whole exome sequencing